Pentingnya Pengetahuan Anatomi Untuk 3D Artist - Anton Sugito Kurniawan (Humaniora, 2011)
No matter how far the current technological advances, anatomical knowledge will still be needed as a basis for making a good character design. Understanding anatomy will help us in the placement of the articulation of muscles and joints, thus more realistic modeling of 3d characters will be achieved in the form and movement. As a 3d character artist, anatomy should be able to inform in every aspect of our work. Each 3D/CG (Computer Graphics)-artist needs to know how to use software applications, but what differentiates a 3d artist with a computer operator is an artistic vision and understanding of the basic shape of the human body. Artistic vision could not easily be taught, but a CG-artist may study it on their own from which so many reference sources may help understand and deepen their knowledge of anatomy.